Improving the Psychological and Pedagogical Competences of the Teaching Staff of Comrat State University in the Lifelong Learning System - Sergei ZAHARIA; Oxana CURTEVA (ACROSS)
In modern society, it is important to improve the quality of the educational process at each stage. There is a need to introduce innovations based on the implementation of the competences approach principles. Comrat State University has a lifelong learning center. Due to the work of European Projects, the implementation of innovations in the system of professional development of specialists has become more effective.